2005
DOI: 10.1063/1.1865325
|View full text |Cite
|
Sign up to set email alerts
|

Refractive indices of ZnSiN2 on r-plane sapphire

Abstract: Articles you may be interested inDispersion properties and low infrared optical losses in epitaxial AlN on sapphire substrate in the visible and infrared range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Among these, ZnGeN 2 and ZnSiN 2 and alloys of ZnSi x Ge 1−x N 2 were grown in thin film form (mostly on sapphire substrates) by a few different approaches, ranging from Cl based vapor growth [3], metalorganic chemical vapor deposition (MOCVD) [8,9], remote plasma MOCVD [10,11,12], RF-sputtering [13] at high pressure by Endo et al [2] and polycrystalline as well as small single crystals were grown by Du et al [14]. Raman spectra were measured by Viennois et al [15] on polycrystalline powders and on small single crystal needles by Peshek et al [16] Optical absorption [17], index of refraction [18], infrared reflectivity [19], magnetic properties upon Mn doping [20], and fabrication of transistors on SiC [21] were investigated for the Zn(Si,Ge)N 2 films obtained produced by Zhu et al [8]. Band structure calculations at the local density approximation (LDA) level were carried out by Limpijumnong et al [22] Misaki et al [23], Shaposhnikov et al [24] and Paudel [25] for a number of these materials but leave considerable uncertainty on the band gaps because of the shortcomings of the LDA.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ZnGeN 2 and ZnSiN 2 and alloys of ZnSi x Ge 1−x N 2 were grown in thin film form (mostly on sapphire substrates) by a few different approaches, ranging from Cl based vapor growth [3], metalorganic chemical vapor deposition (MOCVD) [8,9], remote plasma MOCVD [10,11,12], RF-sputtering [13] at high pressure by Endo et al [2] and polycrystalline as well as small single crystals were grown by Du et al [14]. Raman spectra were measured by Viennois et al [15] on polycrystalline powders and on small single crystal needles by Peshek et al [16] Optical absorption [17], index of refraction [18], infrared reflectivity [19], magnetic properties upon Mn doping [20], and fabrication of transistors on SiC [21] were investigated for the Zn(Si,Ge)N 2 films obtained produced by Zhu et al [8]. Band structure calculations at the local density approximation (LDA) level were carried out by Limpijumnong et al [22] Misaki et al [23], Shaposhnikov et al [24] and Paudel [25] for a number of these materials but leave considerable uncertainty on the band gaps because of the shortcomings of the LDA.…”
Section: Introductionmentioning
confidence: 99%
“…The same group also reported ZnSiN 2 growth and alloy growth of ZnSi 1−x Ge x N 2 growth and these materials were investigated by a number of other collaborators determining optical properties 6,7 , transistor devices on SiC 8 , and even their suitability as magnetic semiconductor host by implantation of Mn 9 . Muth et al 6 determined band gaps from optical absorption data as a function of alloy composition in ZnSi 1−x Ge x N 2 and found it to vary between 3.1-3.2 eV for ZnGeN 2 to 4.4 eV in ZnSiN 2 .…”
Section: Larson Et Almentioning
confidence: 99%
“…Muth et al 6 determined band gaps from optical absorption data as a function of alloy composition in ZnSi 1−x Ge x N 2 and found it to vary between 3.1-3.2 eV for ZnGeN 2 to 4.4 eV in ZnSiN 2 . Cook et al 7 determined the indices of refraction and Mintairov et al 10 determined the infrared reflection relating to the vibrational spectrum.…”
Section: Larson Et Almentioning
confidence: 99%
“…1,2 These studies revealed that ZnGeN 2 is expected to have a direct gap, while ZnSiN 2 is expected to have an indirect band gap. Furthermore, rather than acting as a biaxial crystal as one might suspect from the orthorhombic symmetry, calculations 1 and experiment 9 and have shown the crystal refractive index to have a uniaxial nature. 2 Potentially this matches well with lattice constants of GaN where a=3.189 Å, c= 5.185 Å, and 4H SiC where a=3.073 Å and c=10.53 Å.…”
Section: Introductionmentioning
confidence: 99%